1978
DOI: 10.1002/bms.1200051107
|View full text |Cite
|
Sign up to set email alerts
|

Identification of amino sugars from bacterial lipopolysaccharides by gas chromatography electron impact and chemical ionization mass spectrometry

Abstract: Amino sugars isolated from lipopolysaccharides of Brucella suis, Brucella abortus and Neisseria gonorrhoeae colony types 1 and 4 were identified using gas chromatography electron impact and chemical ionization mass spectrometry. Lipopolysaccharides were obtained by aqueous ether or aqueous phenol extraction. Isolated lipopolysaccharides were hydrolyzed in 1% acetic acid followed by hydrolysis of the polysaccharide moiety in 2 NHCl for 6 h at 100 degrees C. Amino sugars were first isolated by elution from Dowex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1982
1982
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…ion beam contains a metastable excited state. Kr" (4p'4S)+Me(ls'S) 4 Kr't(4p''P,,,)+He' ('S) 11 7 c Kr" (4piJS)+He(l\'S) 4 Kr"(4p4'DZ)+He+ ('S) 10 5…”
Section: Sequential Mass Spectrometry (Ms/mslms) Of the Amino-saccharmentioning
confidence: 99%
“…ion beam contains a metastable excited state. Kr" (4p'4S)+Me(ls'S) 4 Kr't(4p''P,,,)+He' ('S) 11 7 c Kr" (4piJS)+He(l\'S) 4 Kr"(4p4'DZ)+He+ ('S) 10 5…”
Section: Sequential Mass Spectrometry (Ms/mslms) Of the Amino-saccharmentioning
confidence: 99%
“…Monosaccharides have been characterized by electron ionization (EI) [5,6], field desorption (FD) [7][8][9], chemical ionization (CI) [5,6] and fast atom bombardment (FAB) [10] mass spectrometry. Application of desorption chemical ionization (DCI) to glycosides has also been described [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Biomarker m/z 115Of the peaks found in the m/z 115 cluster, only the peak at m/z 115.0641 (C5 H 9 O 2 N) was observed in the carbohydrate standard, N-acetylglucosamine (NAG). The precursor ions of m/z 115.0641 in the B. neotomae spectrum include m/z 143.0598 (C 6 H 9 O 3 N), m/z 185.0711 (C 8 H 11 O 4 N) and m/z 186.0788 (C 8 H 12 O 4 N).…”
mentioning
confidence: 99%
“…However it has been shown that EI-MS of permethylated iV-acetylhexosamines allows the localization of the acetamido group in the C-l, C-2, C-3, or C-4 positions. Moreover, Cl of Me3Si derivatives of some 2-IV-acetyl hexosamine stereoisomers using methane as reactant gas gives mass spectra in which it is the relative intensities of the fragment ions that allows their differentiation (5).…”
mentioning
confidence: 99%